(untitled) (Bangladesh Journal of Botany, 2015)
An experiment was conducted during Kharif seasons of 2009 and 2010 on groundnut (Arachis hypogaea L.) under western dry zone of India following a split-plot design with four dates of sowing (April 20, May 15, June 9 and July 4) and two varieties (HNG 10 and TG 37A) in main- plot and four fertility levels (0, 20 N : 40 P2O5, 30 N : 60 P2O5 and 40 N : 80 P2O5 kg /ha) in sub-plot. Yield component of semispreading variety HNG 10 i.e. pods/plant, number of kernel/pod, seed index, shelling percentage and yields i.e. pod, kernel, haulm and biological yield were statistically at par with each other from April 20 to June 9 sowing and minimum yield was observed in July 4 sowing, while days to maturity reduced significantly with delay sowing. Variety TG 37A sown at July 4 had significantly higher yield attributes and yields than earlier sowing. Harvest index in both the varieties was observed significantly higher in July 4 sowing. Significantly higher yield components and yields were recorded in 30 kg N-60 kg P2O5/ha which was statistically at par with 40 kg N-80 kg P2O5/ha. On the basis of economics, June 9 sowing variety HNG 10 of groundnut recorded significantly higher net return. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21669 Bangladesh J. Bot. 43(2): 169-173, 2014 (September)